Divergence of duplicate genes in exon–intron structure - Xu, Guixia (National Academy of Sciences, 2012)
Gene duplication plays key roles in organismal evolution. Duplicate genes, if they survive, tend to diverge in regulatory and coding regions. Divergences in coding regions, especially those that can change the function of the gene, can be caused by amino acid-altering substitutions and/or alterations in exon–intron structure. Much has been learned about the mode, tempo, and consequences of nucleotide substitutions, yet relatively little is known about structural divergences. In this study, by analyzing 612 pairs of sibling paralogs from seven representative gene families and 300 pairs of one-to-one orthologs from different species, we investigated the occurrence and relative importance of structural divergences during the evolution of duplicate and nonduplicate genes. We found that structural divergences have been very prevalent in duplicate genes and, in many cases, have led to the generation of functionally distinct paralogs. Comparisons of the genomic sequences of these genes further indicated that the differences in exon–intron structure were actually accomplished by three main types of mechanisms (exon/intron gain/loss, exonization/pseudoexonization, and insertion/deletion), each of which contributed differently to structural divergence. Like nucleotide substitutions, insertion/deletion and exonization/pseudoexonization occurred more or less randomly, with the number of observable mutational events per gene pair being largely proportional to evolutionary time. Notably, however, compared with paralogs with similar evolutionary times, orthologs have accumulated significantly fewer structural changes, whereas the amounts of amino acid replacements accumulated did not show clear differences. This finding suggests that structural divergences have played a more important role during the evolution of duplicate than nonduplicate genes.